Renal and pulmonary effects of angiotensin converting enzyme inhibition in chronic hypoxic lung disease. Issue 6 (June 1989) - Oliver, R M; Peacock, A J; Fleming, J S; Waller, D G
Abstract : The effects of 28 days' treatment with captopril or with placebo on renal and pulmonary function were evaluated in nine patients with stable pulmonary heart disease. Captopril (25 mg twice daily) caused a 17% rise in effective renal plasma flow but no change in glomerular filtration rate, resulting in a fall in filtration fraction likely to favour natriuresis. Captopril did not alter FEV1, lung volumes, or arterial oxygen or carbon dioxide tension.